Chip-based digital PCR as a novel detection method for quantifying microRNAs in acute myocardial infarction patients - ROBINSON Samuel; FOLLO Marie; HAENEL David; MAULER Maximilian; STALLMANN Daniela; HEGER Lukas Andreas; HELBING Thomas; DUERSCHMIED Daniel; PETER Karlheinz; BODE Christoph; AHRENS Ingo; HORTMANN Marcus (Acta Pharmacologica Sinica, 2018)
miRNAs have shown promise as potential biomarkers for acute myocardial infarction (AMI). However, the current used quantitative real-time PCR (qRT-PCR) allows solely for relative expression of nucleic acids and it is susceptible to day-to-day variability, which has limited the validity of using the miRNAs as biomarkers. In this study we explored the technical qualities and diagnostic potential of a new technique, chip-based digital PCR, in quantifying the miRNAs in patients with AMI and ischaemia-reperfusion injury (I/R). In a dilution series of synthetic C elegans-miR-39, chip-based digital PCR displayed a lower coefficient of variation (8.9% vs 46.3%) and a lower limit of detection (0.2 copies/μL vs 1.1 copies/μL) compared with qRT-PCR. In the serum collected from 24 patients with ST-elevation myocardial infarction (STEMI) and 20 patients with stable coronary artery disease (CAD) patients after percutaneous coronary intervention (PCI), we used qRT-PCR and multiplexed chip-based digital PCR to quantify the serum levels of miRNA-21 and miRNA-499 as they have been validated in AMI in prior studies. In STEMI, I/R injury was assessed via measurement of ST-segment resolution (ST-R). Chip-based digital PCR revealed a statistical significance in the difference of miR-21 levels between stable CAD and STEMI groups (118.8 copies/μL vs 59 copies/μL; P=0.0300), whereas qRT-PCR was unable to reach significance (136.4 copies/μL vs 122.8 copies/μL; P=0.2273). For miR-499 levels, both chip-based digital PCR and qRT-PCR revealed statistically significant differences between stable CAD and STEMI groups (2 copies/μL vs 8.5 copies/μL, P=0.0011; 0 copies/μL vs 19.4 copies/μL; P